The Digital Dilemma: Balancing Phone Time and Real Life in the Age of Social Media - Susan, Kemigisha (Advances in Social Sciences Research Journal, 2025)
The widespread adoption of smartphones and social media has led to a significant increase in screen time among adolescents. This study investigated the relationship between screen time and mental health in adolescents, with a focus on the impact of screen time on mental health symptoms, social relationships, and productivity. A mixed-methods approach was employed, combining both quantitative and qualitative data collection and analysis methods. The study found that excessive screen time was associated with negative mental health outcomes, including anxiety, depression, and lower self-esteem. Focus group discussions revealed that adolescents experience social pressure to be constantly connected to their screens, contributing to feelings of anxiety and stress. The findings of this study have implications for promoting healthy screen use habits among adolescents, including the need for parents, educators, and healthcare professionals to be aware of the potential negative effects of excessive screen time on adolescents’ mental health.